Tribunal de Contas do Estado da Paraíba como parceiro da administração pública: princípio da eficiência nas atividades típicas e atípicas. - Oliveira, Eduardo Cavalcanti de (2013)
State reform initiated in the 90 states and directs the administration to transform the administrative management of patrimonial and bureaucratic to a management priority on the server and citizens. This new management concept is based on the principles of the Constitution: legality, impersonality, publicity and efficiency. It is observed in this study, the efficiency was implanted in the TCE/PB, will address two separate aspects first, an administrative review, with emphasis on the subjective, which will be studied data obtained from a satisfaction survey held with employees and on the other hand investment in human resources, training and expertise pertaining to employees. In another keynote this work is devoted to the essential function of TCE/PB is the analysis of accounts, we will analyze data on the number of processes proceedings and judged and other important aspects of the report.